IRELAND’S PROPOSED CO-OPERATIVE SOCIETIES BILL 2022 - Carroll, Bridget (International Journal of Cooperative Law, 2023)
In November 2022 the government of Ireland published the General Scheme of the Co-operative Societies Bill, 2022. To date, co-operatives in Ireland have largely made use of the Industrial and Provident Societies Acts (1893-2021) which pre-date the state. The proposed new legislation, which is specific to co-operatives, is significant in scale, consolidating existing provisions and introducing new ones aimed at modernising co-operative governance in areas suchas the legal duties of directors, compliance and financial reporting requirements. It follows an overhaul of the Companies Act and a public consultation exercise.